Genome-wide association mapping and genomic prediction of stalk rot in two mid-altitude tropical maize populations - Junqiao Song; Pacheco Gil, Rosa Angela; Alakonya, Amos; Cruz-Morales, Andrea S.; Muñoz-Zavala, Carlos; Jingtao Qu; Chunping Wang; Xuecai Zhang; San Vicente Garcia, Felix M.; Dhliwayo, Thanda (Elsevier, 2024)
Maize stalk rot reduces grain yield and quality. Information about the genetics of resistance to maize stalk rot could help breeders design effective breeding strategies for the trait. Genomic prediction may be a more effective breeding strategy for stalk-rot resistance than marker-assisted selection. We performed a genome-wide association study (GWAS) and genomic prediction of resistance in testcross hybrids of 677 inbred lines from the Tuxpeño and non-Tuxpeño heterotic pools grown in three environments and genotyped with 200,681 single-nucleotide polymorphisms (SNPs). Eighteen SNPs associated with stalk rot shared genomic regions with gene families previously associated with plant biotic and abiotic responses. More favorable SNP haplotypes traced to tropical than to temperate progenitors of the inbred lines. Incorporating genotype-by-environment (G × E) interaction increased genomic prediction accuracy.